Wireless Sensor System for Recycling - Seppänen, Sami (My University, 2011)
The motivation of this thesis was to research and design a prototype model of a wireless sensor network application, to be used as an automated detection infrastructure in recycling environment. The initial idea was to measure the level of the surface in a recycling container and transmit the information through a wireless communication system. The prototype is an initial step for recycling companies for building an automated detection network. Background of the research strongly supports the accomplished prototype. Study includes description of wireless environment with its problems and challenges. It proceeds with consideration of suitable wireless standards and considers most convenient sensor methods for recycling environment. Eventually document presents the prototype combining the studied entities. As a result, the prototype has two main operating parts: the wireless communication network and sensors. The network was realized with ZigBee standard by using two radio chips as communication nodes. Second communication node is attached to a recycling container and combined with two ultrasound sensors. This node includes a soft-ware algorithm, which is polling the state of the sensors regularly and deciding if the container is full. The node proceeds to transmission of the information to other communication node. This node is connected to computer and will transmit the information to be used by the recycling organization.
Keywords: Wireless sensor network; XBee; Arduino; sensors; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|